The Relationship Among Psychological Factors, Neglect-Like Symptoms And Postoperative Pain After Total Knee Arthroplasty - Yoshiyuki Hirakawa; Michiya Hara; Akira Fujiwara; Hirofumi Hanada; Shu Morioka (Pain Research and Management)
BACKGROUND: Persistent postoperative pain has a significant relationship with patient health and satisfaction.